The Effect of Zumba on Dysmenorrhea in Students of the Faculty of Medicine, Diponegoro University - Humairoh Mutha'alimah; Marijo Marijo; Yuli Trisetiyono; Putri Sekar Wiyati (Jurnal Kedokteran Diponegoro)
Background: Dysmenorrhea is the most common symptom of most menstrual complaints, and has a greater risk of causing disease than any other gynecological complaints. Dysmenorrhea can be accompanied by other symptoms such as sweating, tachycardia, nausea, vomiting, headache, diarrhea and tremors. Dysmenorrhea causes activity limitations which can affect productivity and quality of life of a woman.